ANALISIS METODE CASING WHILE DRILLING UNTUK SETTING CASING 16” PADA SUMUR C2 - Bobby Rifki Saputra; Asri Nugrahanti; Rizki Akbar (Jurusan Teknik Perminyakan Fakultas Teknologi Kebumian dan Energi Universitas Trisakti, 2018)
C2 well is an exploration well located in south sumatera area managed by PT. MEPI in planned CSS field will be drilled to a depth of 12.000 ftTVD vertically. Planning the use of casing while drilling is done by using 16